A backcasting approach for matching regional ecosystem services supply and demand. (January 2016) - Brunner, Sibyl Hanna; Huber, Robert; Grêt-Regamey, Adrienne
Abstract: Ecosystem services (ES) modeling studies typically use a forecasting approach to predict scenarios of future ES provision. Usually, these forecasts do not inform on how specific policy alternatives will influence future ES supply and whether this supply can match ES demand – important information for policy-makers in practice. Addressing these gaps, we present a multi-method backcasting approach that links normative visions with explorative land-use and ES modeling to infer land-use policy strategies for matching regional ES supply and demand. Applied to a case study, the approach develops and evaluates a variety of ES transition pathways and identifies types, combinations and timings of policy interventions that increase ES benefits. By making explicit ES sensitivity towards regional policy strategies and global boundary conditions over time, the approach allows to address key uncertainties involved in ES modeling studies. Highlights: We propose a novel backcasting approach for ecosystem services (ES) assessments. The approach links normative visions with explorative land-use and ES modeling. Modeling ES transition pathways identifies desirable land-use policy strategies. Type, combination and timing of policy interventions influence ES benefits. Effectiveness of policy strategies depends on global boundary conditions.